2005
DOI: 10.1002/fld.937
|View full text |Cite
|
Sign up to set email alerts
|

Large eddy simulation of turbulent flows in complex and moving rigid geometries using the immersed boundary method

Abstract: SUMMARYA large eddy simulation (LES) methodology for turbulent ows in complex rigid geometries is developed using the immersed boundary method (IBM). In the IBM body force terms are added to the momentum equations to represent a complex rigid geometry on a ÿxed Cartesian mesh. IBM combines the e ciency inherent in using a ÿxed Cartesian grid and the ease of tracking the immersed boundary at a set of moving Lagrangian points. Speciÿc implementation strategies for the IBM are described in this paper. A two-sided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…This is shown to result in a consistent set of equations; however, the present work shows that using the pseudo-velocity to define the force density can result in poor satisfaction of the boundary conditions on the surface of the object, which may result in permeability of an impermeable surface. However, the poor satisfaction of boundary conditions on the surface of the object may not greatly impact gross metrics such as drag coefficients; the authors and others [3,7,8,12,15] have computed drag coefficients for blunt body flows such as cylinders and spheres that have closely matched those obtained experimentally and from computational work involving body-fitted meshes. The present work demonstrates that satisfaction of the boundary conditions on the surface of the object is strongly a function of the time step, if the pseudo-velocity is used to define the force density.…”
Section: Introductionmentioning
confidence: 83%
“…This is shown to result in a consistent set of equations; however, the present work shows that using the pseudo-velocity to define the force density can result in poor satisfaction of the boundary conditions on the surface of the object, which may result in permeability of an impermeable surface. However, the poor satisfaction of boundary conditions on the surface of the object may not greatly impact gross metrics such as drag coefficients; the authors and others [3,7,8,12,15] have computed drag coefficients for blunt body flows such as cylinders and spheres that have closely matched those obtained experimentally and from computational work involving body-fitted meshes. The present work demonstrates that satisfaction of the boundary conditions on the surface of the object is strongly a function of the time step, if the pseudo-velocity is used to define the force density.…”
Section: Introductionmentioning
confidence: 83%
“…Though LES has been successfully applied to simulate the turbulence flows with complex geometry [20][21][22], relatively few studies have been reported using LES for simulating the flow in a strong three-dimensional (3D) skew Francis hydro-turbine passage. A few studies of DNS and LES of fully turbulent flow in a low pressure turbine passage have been done, only for two-dimensional (2D) blade cascade simplifications [23][24][25].…”
Section: W Wang Et Almentioning
confidence: 99%
“…The same condition is only first-order accurate in the p-form, but has nonetheless been used in the literature (e.g. [29,14]). Following a similar analysis to Kim and Moin [26], a second order accuracy can be achieved in the p−form by enforcing the immersed boundary condition,û Γ = U n Γ + ∆tGφ n−1 Γ (the derivation is deferred to Appendix A).…”
Section: Governing Equations and Semi-implicit Discretizationmentioning
confidence: 99%